2013
DOI: 10.4269/ajtmh.13-0054
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Study to Assess the Use and Performance of Household Filters in Zambia

Abstract: Abstract. Effective household water treatment can improve drinking water quality and prevent disease if used correctly and consistently over time. One year after completion of a randomized controlled study of water filters among households in Zambia with children 2 years old and mothers who were human immunodeficiency virus (HIV)-positive, we conducted a follow-up study to assess use and performance of new filters distributed at the conclusion of the study; 90% of participating households met the criteria for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The observed reductions in TTC contamination is consistent with other field-based studies of the LifeStraw filter, including version 1.0, a hanging model (Boisson et al, 2010;Peletz et al, 2013Peletz et al, , 2012 and version 2.0, the tabletop model (Rosa et al, 2014b). Levels of faecal contamination in the control arm and in intervention households whose sample did not come from the LifeStraw were similar to other studies in Rwanda among households not using a LifeStraw filter Rosa et al, 2014b).…”
Section: Discussionsupporting
confidence: 79%
“…The observed reductions in TTC contamination is consistent with other field-based studies of the LifeStraw filter, including version 1.0, a hanging model (Boisson et al, 2010;Peletz et al, 2013Peletz et al, , 2012 and version 2.0, the tabletop model (Rosa et al, 2014b). Levels of faecal contamination in the control arm and in intervention households whose sample did not come from the LifeStraw were similar to other studies in Rwanda among households not using a LifeStraw filter Rosa et al, 2014b).…”
Section: Discussionsupporting
confidence: 79%
“…Reductions in use have been found for PuR, boiling, chlorination, and SODIS after six months (83); similar reductions for the ceramic filter in rural Cambodia were mostly attributed to breakage (84). One HWTS exception is a LifeStraw Family filter intervention that targeted HIV-positive mothers in Zambia: Twelve months later, 90% of households reported using the filter (85).…”
Section: Sustained Usementioning
confidence: 77%
“…In a 1‐year follow‐up RCT in Zambia, Peletz et al. () found that 53% of families were not storing their water properly. When water is stored improperly, contamination can occur despite the purity of the water directly after filtering.…”
Section: Literature Reviewmentioning
confidence: 99%